Correlation of Friendship Motive Towards Loneliness on Boarding School Students at DDI Mangkoso - Syamsul, Sulfianti; Widyastuti,; Nur Hidayat, Muh. (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The aim of this research is to determine the correlation of friendship motive towards loneliness on boarding school students. This research was also examinedthe differences level of friendship motive and loneliness on male and female students. Methodology: The subjectsconsisted of 247 students, 172 subjects are male and 75 subjects are female students at boarding school DarudDa'wahwalIrsyad Rahman Ambo DalleMangkoso. This research used product moment pearson test and independent sample t-test. Result: The results showed that there was correlation of friendship motive towards loneliness (p = 0.000). The correlation coefficient of friendship motive toward loneliness was -0.618. The research also revealed that there was no differences level of friendship motive (p=0.731) and loneliness (p=0.150) among male and female students. This research was expected to provide description about friendship motive and loneliness, especially for the student on boarding school.